PENGARUH KEPEMILIKAN KAS, KEBIJAKAN INVESTASI, KEBIJAKAN HUTANG, DAN KEBIJAKAN DIVIDEN TERHADAP KINERJA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Verlinda Fristisya; Hidayat Wiweko (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This paper examines the impact of cash holdings, investment policy, debt policy, and dividen policy on firm perfomance of consumer goods industry sector company listed on the Indonesia Stock Exchange in the period 2016 to 2020 with control variabels firm size and sales growth. Sampling technique with purposive sampling method obtained 35 sample companies. Accordingly, with a panel data and common effect model to regression model the results of the study indicated that cash holdings, investment policy, debt policy, and dividen policy have a positive impact on firm performance. Variabel controls firm size does not impact on firm performance and sales growth has a positive impact on firm performance.